1997
DOI: 10.1159/000201427
|View full text |Cite
|
Sign up to set email alerts
|

Patency of the Human Accessory Pancreatic Duct as Determined by Dye-Injection Endoscopic Retrograde Pancreatography

Abstract: The accessory pancreatic duct (APD) is the smaller and less constant pancreatic duct. The patency of the APD was investigated clinically in an effort to determine its role in pancreatic pathophysiology. Dye-injection endoscopic retrograde pancreatography (ERP) was performed in 190 cases. In the patients who exhibited filling of the fine branches of the ducts on ERP, contrast medium with indigo carmine was injected into the major duodenal papilla. The patency of the APD was determined by observing the excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 4 publications
3
39
0
Order By: Relevance
“…Long inferior branches exceeding 2聽cm and passing through the MPD to the caudal portion were examined. The terminal portions of the APD could be classified radiologically into stick, branch, saccular, spindle or cudgel types [8, 9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long inferior branches exceeding 2聽cm and passing through the MPD to the caudal portion were examined. The terminal portions of the APD could be classified radiologically into stick, branch, saccular, spindle or cudgel types [8, 9]. …”
Section: Methodsmentioning
confidence: 99%
“…After conventional ERP, we performed the dye injection ERP [8, 9]to evaluate the function of the APD in 109 patients in whom the MPD could be selectively cannulated and a pancreatogram of the fine branches could be obtained. First, 2 or 3聽ml of contrast medium containing indigo carmine were injected through a catheter into the MPD with the usual injection pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The spindle- and cudgel-type APD showed higher patency, but the branch- and saccular-type APD showed lower patency than the stick-type APD. We also found that patency of the APD in patients with acute pancreatitis was significantly lower than in controls [5,6,7]. …”
Section: Discussionmentioning
confidence: 93%
“…Using dye injection ERP, we previously demonstrated the close relationship between the terminal shape of the APD and its patency in 291 control cases. We also found that patency of the APD was significantly lower in 46 patients with acute pancreatitis than in controls [5,6,7]. To examine whether patency of the APD prevents post-ERCP pancreatitis, we retrospectively determined patency of the APD in patients with post-ERCP pancreatitis based on the previous data by dye injection ERP.…”
Section: Introductionmentioning
confidence: 99%
“…We have prospectively studied the anatomy of the pancreatic duct system using endoscopic retrograde pancreatography [6,7,8,9]. To achieve optimal visualization, several pancreatograms of the head of the pancreas were taken with the patient in the prone or slightly oblique position.…”
Section: Methodsmentioning
confidence: 99%